Techno-literature: Interactive Arabic novel — Chat Novel by Muhammad Snaijla as a model - allia, assia; henka, laid; korbaa, ali; khelfaoui, farid (El Omda in Linguistics and Discourse Analysis, 2025)
The significant development experienced by the Arabic novel during the twentieth century, through its appropriation of various forms of traditional Arabic narrative and its benefit from the experiences and techniques of the Arabic novel, enabled it to reach a certain level of professionalism. However, with the onset of the digital revolution in the 1970s, advanced societies entered the postmodern era, which made developing countries, particularly Arab countries, required to keep pace with the new demands of the era. The same applies to the Arabic novel, which has itself become compelled to enter the era of digitalization and the information revolution, marking the beginning of the emergence of the Arabic interactive novel pioneered by Muhammad Snaijla.